Understanding the Role of Ethical Leadership and Workplace Conflicts a Mediation Moderation Model: A Time-Lagged Study - Ayesha Rashid; Muhammad Hassan (iRASD Journal of Management)
Drawing on Social Learning Theory and Conservation of Resource Concept this research mediation moderation model was supported by a study which is conducted from multiple sources and a study conducted in three-waves in Pakistan. Workplace Conflicts and Ethical Leadership ideas are developed and brought together by these results. This exploration inspected the character of Ethical leadership happening in workplace conflict circumstances. Explicitly, ethical leadership remained prophesied on the way to construct members’ resolution efficacy and consequently upsurge members’ capability to agreement through conflict state of affairs (i.e., relationship and task conflicts) concerning in the workplace political scenarios. We gathered information from a variety of sources, including employees and their direct managers in several Pakistani organizations. The current study employed the survey approach. This study shows a negative relationship between ethical leadership and relationship conflict and task conflicts. Moreover, this study also shows, resolution efficacy plays a role as a mediator between Ethical Leadership and relationship conflict as well as task conflicts. Furthermore, shows that Perception of Politics plays a role as a moderator in the relationship between Resolution Efficacy and Relationship Conflicts as well as task conflicts. Ethical leadership activities possibly will improve employee conflict resolution efficacy, implying that concluded the solicitation of ethical leadership social learning philosophies, leaders may be critical in creating a work environment that morally encourages and fosters employees' conflict resolution efficacy.